Potentiating effect of imidacloprid on arsenic-induced testicular toxicity in Wistar rats - Lakshay Mahajan; Pawan Kumar Verma; Rajinder Raina; Shilpa Sood (BMC Pharmacology and Toxicology, 2018)
Abstract Background It is an established fact that humans and animals are exposed to more than one chemical concurrently from various sources such as food, air and water. In the past, much emphasis was laid on evaluating the toxic effects of a single chemical. Nowadays an increased attention is being paid to the interaction of xenobiotics with one another. Therefore, a study was aimed to evaluate the potentiating effect of imidacloprid (IMI) on arsenic-induced testicular toxicity in rats. Methods Adult male Wistar rats randomly divided into eight groups with six in each were subjected to daily oral administrations for 28 days. Group I served as control, group II received IMI at the dose rate of 16.9 mg/kg body weight, group III, IV and V received arsenic at the dose rate of 50, 100 and 150 ppb in drinking water whereas group VI, VII and VIII received both arsenic and IMI. Results Repeated oral administrations of IMI or arsenic (150 ppb) alone resulted in a significant (P < 0.05) elevation in the levels of malondialdehyde (MDA) and advanced oxidation protein product (AOPP) along with significant (P < 0.05) decline in total thiols and antioxidant enzymatic activities indicating reduced antioxidant defense in testicular tissue of exposed rats. These findings were further corroborated with histological alterations in testes like fluid accumulation in interstitial spaces in IMI administered rats. Similarly, rats provided access exclusively to arsenic-containing drinking water induced degenerative changes in seminiferous tubules in a concentration-dependent manner. Concurrent administration of IMI and arsenic produced more severe antioxidant and histopathological alterations of testes as compared to exposure to either toxicant. Conclusions Reduced antioxidant activities, increased MDA and AOPP levels with severe histopathological alterations in testes of rats on concurrent exposure indicated that IMI potentiated the arsenic-induced testicular toxicity in Wistar rats.